Egypt 2023 - Lee, Jessica (Travel writer); Hardy, Paula, 1973-; Keith, Lauren; Walker, Jenny (Jenny Fiona Hawkes) (Lonely Planet guidebooks., 2023)
Lonely Planet's Egypt is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Discover the pyramids of Giza, cruise the Nile, and dive in the Red Sea; all with your trusted travel companion. Get to the heart of Egypt and begin your journey now!